Microbiological of water from semiartesian wells in rural Aparecida D’Oeste, São Paulo, Brazil - Correa, Glauder; Oliveira, Luciano Ricardo de; Kozusny-Andreani, Dora Inés; Américo-Pinheiro, Juliana Heloisa Pinê; Frias, Danila Fernanda Rodrigues (Revista Verde de Agroecologia e Desenvolvimento Sustentável, 2020)
The quality and safety of water are important factors for public health, as it can serve as a carrier of pathogens that cause various diseases in humans and animals. The objective of the research was to evaluate the microbiological quality of water from semiartesian wells in the rural area of Aparecida D’Oeste, São Paulo, and to verify the main factors associated with its contamination. The study was carried out in 50 rural properties. The samples were collected in a 1000 mL sterile in glass bottle with a lide, at the well outlet valve, after a previous pumping of 10 minutes. The samples were submitted to the determination of the presence of total coliforms, thermotolerant coliforms and count of mesophilic microorganisms. For counting mesophiles, total coliforms and thermotolerants, were used Soy Triptone Agar, Lauril Sulfate Broth, Brilliant Green Broth and Levine Agar. Colonies that have not been identified as Escherichia coli have been subjected to biochemical tests. During the dry season, 31 properties (62%) presented mesophiles, 39 total coliforms (78%) and 14 thermotolerant coliforms (28%), these being E. coli, Klebsiella spp., and Enterococcus spp. In the rainy season, 21 properties (42%) presented mesophiles, 33 total coliforms (66%) and 7 thermotolerant coliforms (14%), these being E. coli, Klebsiella spp, Enterococcus spp., Proteus spp. and Salmonella spp. It can be concluded that there is contamination in the waters of semiartesian wells and that it is of great importance to promote educational work to the population on the importance of water quality and waterborne diseases.